ПРОФЕСІЙНО-ПЕДАГОГІЧНА КОМПЕТЕНТНІСТЬ ЯК КОМПОНЕНТ ФАХОВОЇ ПІДГОТОВКИ МАЙБУТНІХ МЕНЕДЖЕРІВ ЕКОНОМІКИ (Педагогіка вищої та середньої школи, 2007)
The different definitions of “competency” and “competence” are analyzed in this article. An integral model of a prospective manager in economics is defined to be effective in combined competency integration which is necessary to fulfill a specific task and to provide labour resources’ mobility in this sphere.